He Kupu Tuku Iho Mō Tēnei Reanga: A Critical Analysis of Waiata and Haka as Commentaries and Archives of Māori Political History - Ka'ai-Mahuta, Rachael Te Āwhina (Auckland University of Technology, 2010)
Prior to the arrival of Pākehā to Aotearoa/New Zealand, the Māori language was exclusively oral. However, this did not in any way impede the archiving of knowledge and history deemed important by tīpuna Māori. In fact, tribal history, knowledge and traditions have been preserved for generations in the many waiata and haka composed throughout the country. Māori waiata are one example of a traditional medium for the transmission of knowledge including tribal history, politics, historical landmarks, genealogy and environmental knowledge while also acting as a traditional form of expression for the articulation of anger, hatred, sadness, love and desire. Waiata and haka are examples of Māori poetry and literature. They are important for the survival of the Māori language and culture. In this sense, waiata are bound to Māori identity and the identity of whānau, hapū and iwi. Waiata and haka have been likened to the archives of the Māori people, preserving important historical and cultural knowledge, and it is logical that in traditional Māori society these compositions would have acted as the 'newspapers' and perhaps even tribal philosophical doctrine of the time. Waiata offer an alternative view of the history of Aotearoa/New Zealand to those that are based on mainstream Eurocentric history books and archives. However, many of these waiata are being lost through time and with them, a Māori knowledge base regarding the meaning behind the words. This is exaggerated by the fact that waiata contain the highest form of language utilising proverbs and figurative speech. The purpose of this research is to establish the validity of waiata and haka as commentaries and archives of Māori political history. It has included the development of a proposal and template for an online digital repository of waiata that will include not only the music and lyrics but also an in-depth analysis of the meaning behind the lyrics. The site will be free to access and act as an archive to preserve oral histories contained within waiata. This will provide a national resource thus demonstrating the interface between recovering traditional knowledge and storing this through innovative technology especially, for future generations.
Keywords: Waiata; Haka; Politics; Maori; Song; Poetry; History; Tradition; Indigenous; Reo; Language